Fast diagnostic test for familial Mediterranean fever based on a kinase inhibitor. Issue 1 (9th October 2020) - Magnotti, Flora; Malsot, Tiphaine; Georgin-lavialle, Sophie; Abbas, Fatima; Martin, Amandine; Belot, Alexandre; Fauter, Maxime; Rabilloud, Muriel; Gerfaud-Valentin, Mathieu; Sève, Pascal; Duquesne, Agnes; Hot, Arnaud; et al.
Abstract : Background and objective: Familial Mediterranean fever (FMF) is the most frequent hereditary autoinflammatory disease. Its diagnosis relies on a set of clinical criteria and a genetic confirmation on identification of biallelic pathogenic MEFV variants. MEFV encodes pyrin, an inflammasome sensor. Using a kinase inhibitor, UCN-01, we recently identified that dephosphorylation of FMF-associated pyrin mutants leads to inflammasome activation. The aim of this study was to assess whether quantifying UCN-01-mediated inflammasome activation could discriminate FMF patients from healthy donors (HD) and from patients with other inflammatory disorders (OID). Methods: Real-time pyroptosis and IL-1β secretion were monitored in response to UCN-01 in monocytes from FMF patients (n=67), HD (n=71) and OID patients (n=40). Sensitivity and specificity of the resulting diagnostic tests were determined by receiver operating characteristic curve analyses. Results: Inflammasome monitoring in response to UCN-01 discriminates FMF patients from other individuals. Pyroptosis assessment leads to a fast FMF diagnosis while combining pyroptosis and IL-1β dosage renders UCN-01-based assays highly sensitive and specific. UCN-01-triggered monocytes responses were influenced by MEFV gene dosage and MEFV mutations in a similar way as clinical phenotypes are. Conclusions: UCN-01-based inflammasome assays could be used to rapidly diagnose FMF, with high sensitivity and specificity.